(untitled) (Research, Society and Development, 2021)
For decades, HIV infection has affected people all over the world, regardless of social class, gender, sexual orientation, culture or age. More than half of the new reported cases of HIV infections that occur today affect young people aged 15 to 24 years. To guide this literature review, the following question was elaborated: In the literature analyzed, what are the main difficulties faced with regard to the prevention of HIV infection in the young Brazilian population? And the objective was to identify the contributing factors that hinder the prevention of the HIV virus in the young population in Brazil and the means used to approach this group. To achieve the research objective, we opted for the design of a narrative bibliographic research, using articles in Portuguese, covering the topic, available in full databases, published in the period from 2011 to 2021. It should be noted that the greatest difficulties in preventing the HIV virus in the young population are related to the vulnerabilities that this group is exposed to. As for the educational practices, all those presented in the review proved to be efficient, since innovative methods, seeking to draw the attention of the target audience, were well accepted and had the active participation of those involved. Finally, it was possible to observe that most of the productions published in the time frame proposed by this review are aimed at presenting the vulnerabilities of the young public to HIV, and that they highlight the importance of public policies more focused on this public.